PENGUPASAN HUKUM PASAR MODAL SYARIAH TERHADAP HUKUM ISLAM - Rifyal Zuhdi Gultom; Asep Nur Imam Munandar (Institut Bisnis Muhammadiyah Bekasi, 2022)
This research will discuss various types of Islamic sharia law that explore the Islamic Capital Market law. This law is based on the Fatwa of the National Sharia Council, Al Quran, Al Hadith and other laws regulated in Islamic sharia. Stripping the law of the is scrutinized through the verses of the Koran, Al Hadith, and the DSN MUI Fatwa. Other basic Islamic laws will not be examined but will provide additional theory and insight into Islamic law governing the Islamic capital market. In discussing Islamic capital market law on Islamic law, it is carried out using research methods based on references, library literature is followed by carrying out a normative juridical approach that is based on legal norms applied by the MUI DSN Fatwa. In addition to the law of fatwas, research is carried out based on sharia law based on the Koran such as Surah Al Baqarah (2:275), Surah An Nisa (4:29), Surah Al Maidah (5:1), Surah Al Jumuah (62:10) by stripping Islamic capital market legal research is also carried out based on the hadith of Rasulullah SAW which regulates the basis for implementing capital markets. With the stipulation of sharia law guided by the DSN-MUI fatwa No. 40/DSN- MUI/X/2003 in which the DSN-MUI fatwa contains a discussion on regulating the Capital Market with the backing of applying Islamic religious principles correctly to the laws that have been described.